Constipation that needs attention: late Hirschsprung disease - Kristin Agustina; Ni Nyoman Margiani; Pande Putu Yuli Anandasari; Ni Made Mahastuti (DiscoverSys Inc., 2021)
Background: Hirschprung disease (HD) or congenital aganglionic megacolon is an intestinal motor disorder that occurs in approximately 1 in 5000 live births. It makes colon fail to relax, mainly producing the symptoms of constipation. Approximately 90% of cases are diagnosed in the first year of life. Most of the remaining 10% are made in early childhood, with less than 1% being made in teenagers or adulthood.Case report: A 13 years old girl reported to the pediatric surgical outpatient department complaining constipation since birth. There was no history of delayed passage of meconium. A contrast enema study with water-soluble contrast showed high probability of ultrashort segment HD. Histopathological examination revealed neither nerve fibers with ganglion cells nor hypertrophy of nerve fibers were seen confirming the aganglionosis. Surgical treatment was performed with good clinical progression. Conclusion: Despite of its rarity, the possibility of HD should be considered in teenagers with chronic refractory constipation, especially when there was a history of delayed or non-passage of meconium after birth. An accurate diagnosis is mainly based on collective assessment of medical history, clinical examination, contrast enema study, and rectal biopsy as a gold standard.